Implementasi Nilai Moderasi Beragama dalam Buku Pendidikan Agama Islam dan Budi Pekerti pada Peserta Didik Kelas V SD Negeri 75 Lembanna Sinjai Barat - Andi Faiza Firdasari; A Marjuni; Usman (Primer Edukasi Journal, 2023)
This research aims to: (1) Describe the value of religious moderation in the PAI and Character Books for Class V SD/MI. (2) Describe the implementation of the value of religious moderation in Islamic Religious Education Books for Class V students at SD Negeri 75 Lembanna. (3) Knowing what are the obstacles and solutions for PAI teachers in teaching the value of religious moderation at SDN 75 Lembanna Sinjai Barat. The type of research used is a type of qualitative research using a descriptive research design. Methods of data collection is done by observation, interviews, and documentation. The results of this research show that the PAI and Moral Books for class V SD/MI contain several values of religious moderation that can be instilled in students from an early age; The value of religious moderation in fifth grade students at SDN 75 Lembanna as a whole has been well implemented; The teacher's obstacles in teaching religious moderation are the lack of learning media, the background of the students, the appearance of games and shows that are less educational, the lack of interest in students' learning. then, the solution given by the teacher is a varied learning method, giving special advice and attention, connecting with the parents of students, and providing games between lessons.